Pengaruh Kompetensi Aparatur Desa, Kejelasan Sasaran Anggaran, Komitmen Organisasi, Dan Sistem Pengendalian Intern Terhadap Akuntabilitas Pengelolaan Dana Desa Pada Pemerintahan Desa Se-Kecamatan Selemadeg Barat Kabupaten Tabanan - Parastuti, Ni Luh Putu Nita; Sumadi, Ni Komang; Putra, I Putu Deddy Samtika (Hita Akuntansi dan Keuangan, 2025)
This research explores the influence of Village Apparatus Competence, Clarity of Budget Targets, Organizational Commitment, and Internal Control System on Accountability of Village Fund Management in West Selemadeg District, Tabanan Regency. By using a quantitative approach, this research found that all of these independent variables have a positive and significant influence on accountability. The results of the analysis show that Village Apparatus Competence (? = 0.653), Clarity of Budget Targets (? = 0.237), Organizational Commitment (? = 0.310), and Internal Control System (? = 0.256) contribute significantly to increasing accountability in village fund management. This research also notes limitations such as the use of only four variables and the long time for distributing questionnaires, and recommends the development of other variables, training of village officials, budget evaluation, joint activities to increase commitment, and strengthening the internal control system to increase the effectiveness of village fund management.